INTERNAL AND EXTERNAL HARMONY AMONG THE FAITHFUL: INTERPRETATION OF ĀLI ‘IMRĀN: 103 AND AL-SHŪRĀ: 13 - Dika Purnama Aulia Rohma (Ma'had Aly As'adiyah Sengkang, 2025)
This paper aims to explore the values of unity in the Qur'an to build internal and external harmony among religious communities. This study uses a library method with a thematic interpretation approach to QS. Āli ‘Imrān [3]:103 and QS. al-Shūrā [42]:13. The findings of this study indicate that these two verses provide a complete foundation for achieving harmony. Internally, QS. Āli ‘Imrān [3]: 103 emphasises a good relationship with Allah through the Qur'an, a good relationship with other creatures through ukhuwah Islamiyah (Islamic brotherhood), and avoiding fanaticism. Externally, QS. al-Shūrā [42]: 13 teaches harmony by practising one's respective religious teachings, building ukhuwah basyariyah and wathaniyah, and conveying the truth without coercion.